Impact of Soils on the Quality of Grapes from Two Vine Varieties [Vitis Vinifera L. (Vitaceae)] Produced in Côte D'ivoire - Yao, Kouakou Thomas; Coulibaly, Souleymane; Gogbeu, Dan Gbongué Lucien; Konan, Yao Kouakou François; Kouakou, Tanoh Hilaire (Discoveries in Agriculture and Food Sciences, 2023)
Production remains closely linked to its terroir (climate, soil, grape variety and human activity), which sometimes affects the organoleptic qualities of derived products such as wine. Against this backdrop, a study was carried out in Côte d'Ivoire to assess the impact of four agro-ecological zones on the quality of the grapes produced. Grapes from two grape varieties (Béquignol and Aleatico) were harvested in four different agro-ecological zones (Abidjan, Aboisso, Man and Korhogo). A number of biochemical parameters, such as sugar and total phenol content, as well as purification of these compounds, were carried out. The results showed that the total sugar and polyphenol contents of the different grape varieties were higher at the Man site.